Ghosts of Achilles: Heroic Epiphanies Between Myth and Cult (Minerva, 2017)
The starting point of this article is the analysis of selected literary passages documenting Achilles’ epiphanies in the Troad and in the Northern Black Sea coast, particularly in the island of Leuke. In ancient times these two sites were identified respectively as the grave and the posthumous destination of the hero, and the texts confirm that both had a local cult of Achilles. However, the existence of such a cult has been proved only in the island of Leuke, where a numerous votive inscriptions in honor of the hero was found, the most ancient ones dating from the late 6th century B.C. The study of these inscriptions suggests a cultual characterization of Achilles centred on oracular functions and on some particular powers related to the sea. These two aspects are also present in the mythical accounts of the epiphanies of Achilles, which leads us to suggest that these stories could help promote or strengthen the belief in a real power of the hero in these places.
Keywords: Achiles; Troas; Leuke; heroic cult